Mindset Training in Entrepreneurship at Pondok Pesantren Darul Mutaqien 1 - Suryani, Ela; Priyanto, Yuwono; Adjie, Jeannet Kunta (Eastasouth Journal of Positive Community Services, 2023)
To open a mindset, form a strategy indoing entrepreneurship, have a sense and spirit ofindependence and cooperation for students andstudents, and provide material aboutentrepreneurship at Darul Muttaquien 1 IslamicBoarding School.This information is given tostudents and students at the Darull Mutaqien 1Islamic boarding school so that they can participatein creating entrepreneurial businesses and have achallenge in the world of work which is increasinglycompetitive and has high responsibility. In carryingout an entrepreneurial strategy that must be knownby students who want to start entrepreneurship, namely having a strategic location such as on the side of the road, close to a factory, and which mustbe developed to be successful as an entrepreneursuch as integrity, perseverance, self-confidence,responsibility. To become an entrepreneur or to start a business, one must be willing to take risks tocompete and spread the gospel of entrepreneurship in society.